2017
DOI: 10.1371/journal.pone.0179936
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the binding mode of MEK type-III inhibitors. A step towards discovering and designing allosteric kinase inhibitors across the human kinome

Abstract: Protein kinases are critical drug targets for treating a large variety of human diseases. Type-III kinase inhibitors have attracted increasing attention as highly selective therapeutics. Thus, understanding the binding mechanism of existing type-III kinase inhibitors provides useful insights into designing new type-III kinase inhibitors. In this work, we have systematically studied the binding mode of MEK-targeted type-III inhibitors using structural systems pharmacology and molecular dynamics simulation. Our … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…S2-A), we hypothesized that 6-OH may be capable of directly inhibiting MEK1. To test this hypothesis, and gain insight into the plausibility of 6-OH acting as a small molecule kinase inhibitor, we conducted ligand-protein docking simulations using published crystal structures of MEK1 and 6-OH as well as a commercial inhibitor, PD0325901 (PD) (a type-III non-ATP competitive inhibitor, which are well studied (64,65)). Utilizing AutoDock Vina (66), which evaluated energetically optimized binding poses for each ligand, we found that both 6-OH and PD were placed around the well-characterized allosteric binding pocket for this type of inhibitor, without providing prior information on the binding surface.…”
Section: -Oh-bde-47 Is a Promiscuous Kinase Inhibitormentioning
confidence: 99%
“…S2-A), we hypothesized that 6-OH may be capable of directly inhibiting MEK1. To test this hypothesis, and gain insight into the plausibility of 6-OH acting as a small molecule kinase inhibitor, we conducted ligand-protein docking simulations using published crystal structures of MEK1 and 6-OH as well as a commercial inhibitor, PD0325901 (PD) (a type-III non-ATP competitive inhibitor, which are well studied (64,65)). Utilizing AutoDock Vina (66), which evaluated energetically optimized binding poses for each ligand, we found that both 6-OH and PD were placed around the well-characterized allosteric binding pocket for this type of inhibitor, without providing prior information on the binding surface.…”
Section: -Oh-bde-47 Is a Promiscuous Kinase Inhibitormentioning
confidence: 99%
“…Since the discovery of the first ERK experimental inhibitor PD98059 20 years ago [ 8 ], new MEK inhibitors occupying highly specific allosteric sites of the target molecules have provided the opportunity to achieve higher selectivity and have also contributed to validate MEK as a cancer drug target [ 9 ]. Two allosteric MEK inhibitors have received regulatory approval for the treatment of human cancers, namely trametinib and cobimetinib, in a protein kinase-specific drug discovery that continues today [ 10 ]. Finally, therapies that associate BRAF inhibitors with MEK inhibitors (dabrafenib with trametinib and vemurafenib with cobimetinib) are the current treatment strategies for BRAF -mutant advanced cancers, including melanoma [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The unique structural features adjacent to the ATP-binding site of MEK1/2 have been used to identify compounds that inhibit MEK1/2 activity and may have applications targeting other kinases. Zhao et al have presented an excellent review of the type III kinase inhibitor-binding mode with a focus on interactions with MEK1/2 proteins [ 11 ]. These studies provide evidence that unique structural features in catalytic/kinase domains can be exploited to design more selective kinase inhibitors.…”
Section: Part A: Type III Kinase Inhibitorsmentioning
confidence: 99%
“…The activation loop of the MEK1/2 proteins is unique in that it forms a short helix that allows specific interactions with type III inhibitors [ 4 ]. While the activation loop is typically disordered in kinases where structural information is available, other kinases including p38α MAP kinase and B-Raf kinase, along with MEK1/2, have been reported to adopt these short helix structures in the activation loop [ 11 ]. Thus, this unique structural feature could be used to develop type III inhibitors for other kinases.…”
Section: Part A: Type III Kinase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation